2019
DOI: 10.1177/1847980419853159
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nano-carbon by in-liquid plasma method and its application to a support material of Pt catalyst for fuel cell

Abstract: One of the applications of nano-carbon is a support material of platinum (Pt) catalyst for fuel cells. In this study, the nanocarbon was successfully synthesized by in-liquid plasma in ethanol. The synthesized nano-carbon was characterized by the transmission electron microscope and the Raman spectroscopy. Moreover, the nano-carbon was applied to a support material of Pt catalyst for a proton exchange membrane fuel cell. The formation of the Pt particles on the nano-carbon was also carried out using the in-liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Since the in-solution plasma is immersed in the solution, only reactions between the plasma and the solution occur in their entirety. Many recent papers about synthesis methods using in-solution plasma have mostly been reported on the formation of NPs [ 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ].…”
Section: Synthesis Methods Using Liquid-type Precursorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the in-solution plasma is immersed in the solution, only reactions between the plasma and the solution occur in their entirety. Many recent papers about synthesis methods using in-solution plasma have mostly been reported on the formation of NPs [ 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ].…”
Section: Synthesis Methods Using Liquid-type Precursorsmentioning
confidence: 99%
“…Hyun et al [ 103 , 104 ], Panomsuwan et al [ 105 ], Morishita et al [ 106 ], Lee et al [ 107 ], Li et al [ 108 ], Tipplook et al [ 109 ], and Lee et al [ 91 ] used in-solution plasma systems generated by the plasma discharge between tungsten pin-to-pin electrodes, and Alsaeedi et al [ 110 ] chose carbon rods as the electrodes, as shown in Figure 10 , Figure 11 and Figure 12 . Hyun et al used a pair of tungsten electrodes 1 mm in diameter to generate the in-solution plasma; these electrodes were located at a distance of 1.5 mm from the glass reactor.…”
Section: Synthesis Methods Using Liquid-type Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuel cell technologies are new, attracting more attention as energy conversion tools targeting elimination of the fossil fuel pollution, 1,2 whereas fuel cell gives electricity with efficiency above 50% and can provide high power density for a long time at low operating temperatures. 3 Direct methanol fuel cells (DMFCs) are polymer electrolyte fuel cells having some advantages, such as methanol, as fuel has high hydrogen to carbon ratio (4:1), the simple design of the DMFC, and its eco-friendly impact.…”
Section: Introductionmentioning
confidence: 99%
“…1,7 –9,13 –17 In addition, it should be noted that metal–carbon–polymer nanocomposite films may exhibit interesting pressure-sensitive, catalytic, and gas sensing properties and are promising candidates for the realization of efficient flex, catalytic, and gas sensor devices. 18 21…”
Section: Introductionmentioning
confidence: 99%